Entrepreneurial intentions amongst university students in Pakistan: a comparison between students of Islamic and conventional business studies. (8th August 2022) - Shah, Syed Alamdar Ali; Sukmana, Raditya; Ahmad, Muhammad Ali; Saud, Muhammad; Fianto, Bayu Arie
Objective of this research is to examine intentions of entrepreneurship amongst students of Islamic and non-Islamic business studies in Pakistan. Data of 344 respondents from HEC recognised universities in the province of Punjab has been collected and analysed using Cramer's V test to analyse various associations. Results suggest that students pursuing non-Islamic business studies and Islamic studies are more inclined to initiate their businesses after studies as compared to students who have studied Islamic business as a subject or have pursued Islamic business studies as a whole. Students of Islamic business studies have very low inclination towards starting their own business. This research puts forward a new area of research to find dynamics of differences in entrepreneurial intentions between Islamic and non-Islamic graduates.